Old‐age Poverty in Indonesia: Measurement Issues and Living Arrangements. Issue 6 (27th September 2017) - Priebe, Jan
ABSTRACT: Drawing on several rounds of nationally representative household survey data for Indonesia, this article shows that poverty rates among the elderly are substantially higher than those of the rest of the population. Using sensitivity checks on adult equivalence scales and economies of scale, the author demonstrates that the gap in poverty rates between the elderly and non‐elderly population would increase even further if moderate changes to the per‐consumption expenditure assumption were made. Additional panel data evidence reveals that about one‐third of the elderly population is currently vulnerable to poverty. While the findings do not show gender differences in old‐age poverty rates, they do highlight important differences in living arrangements across gender, with the majority of elderly women being widows while the majority of men are still married at all ages.